Challenges and strategies for electricity market transition in China. (October 2019) - Lin, Jiang; Kahrl, Fredrich; Yuan, Jiahai; Liu, Xu; Zhang, Weirong
Abstract: China is currently pursuing electricity reforms that will create wholesale markets for electricity. Electricity markets hold considerable promise for facilitating China's transition to clean energy systems, but face obstacles. The most significant obstacle to market reforms is their potential financial impact on coal generation, which currently accounts for most of China's generating capacity. In this paper, we examine the impact of market reforms on coal generation in China, using Guangdong Province as a case study. We find that, in the near term, market prices are likely to lead to significant decreases in net revenues for coal generators relative to the current benchmark tariff, with 40%–60% of coal generation capacity unable to cover the cost of remaining in commercial operation. We estimate that existing coal generators in Guangdong had 94 billion yuan (US14 billion) in outstanding debt in 2016, creating large risks for banks and raising questions about the potential impacts of electricity market reforms on China's financial industry. The impact of market reforms on coal generators creates two problems—transition and resource adequacy. The development of mechanisms for long-term resource adequacy provides a common solution to both of these problems. Highlights: Market prices likely lead to significant decreases in net revenues for coal generators. Existing coal generators in Guangdong had US14 billion in outstanding debt in 2016. Market reforms create transition and resource adequacy challenges for coal generators. Developing long-term resource adequacy mechanisms can solve both challenges.